High-resolution atomic force microscopy and current-voltage characterisation of DNA and protein complexes. - Emma Davies (2006)
Using the technique of non-contact atomic force microscopy (NC-AFM), the structural properties of DNA and protein complexes were studied at the singlemolecule level and at high-resolution. The electrical properties of these biomolecules were then investigated using an electrode setup. This work focussed on the visualisation of DNA strands, nucleosomes, PUT3 protein and DNA-PUT3 complexes and the effect of protein on the conductivity of DNA. NC-AFM experiments were performed in vacuum and results were compared to tappingmode AFM (TM-AFM) experiments performed in air. The detailed structure of DNA strands 2-kilobase-pairs (kbp) in length, deposited on gold substrates, was observed for the first time using NC-AFM without the need for chemical- anchoring techniques. Measurements made on individual DNA molecules revealed a strand length of 700 nm which was in good agreement with the calculated length of 680 nm for a liner 2-kbp DNA molecule. The average height of the DNA was 1.37 nm compared to 2 nm as determined with X-ray crystallography. Images of nucleosomes on mica revealed unprecedented detail with line profiles indicating peaks of 3-4 nm corresponding to DNA wrapped twice around the nucleosome core. DNA-PUT3 complexes were observed using a very high spring constant cantilever for NC-AFM. The measured diameter of PUT3 was 70 nm with corresponding height ~11 nm. Similar diameters were recorded using TM-AFM but with lower height ~2-2.5 nm. The difference in height is possibly attributed to the non-invasive nature of NC-AFM compared to tapping-mode which may have compressed soft samples into the surface. Current- voltage (I-V) measurements were performed on DNA-PUT3 samples and those prepared in binding buffer gave elevated currents at +5 V (I = 73-115 nA) compared to samples containing an equivalent concentration of DNA prepared with water (I = 0.4-3.6 nA). The presence of binding buffer appeared to improve current readings possibly by interacting with molecules via 'doping' to give to metallic-DNA (M-DNA) or by promoting DNA-PUT3 complex formation. The preferential bonding of DNA-PUT3 complexes to gold electrodes is suggested as a possible interpretation.